UNATTRACTIVE INCENTIVE: THE CASE OF TAX ALLOWANCE POLICY IN INDONESIA’S SHIPYARD INDUSTRY - Aditya Putra; Akhmad Solikin (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2018)
This study aims to analyze the achievement of policy objectives in terms of effectiveness, efficiency, adequacy, neutrality, resposiveness, and accuracy of income tax incentives in the form of tax allowances for the Indonesia’s shipyard industry. This study also evaluate the achievement of the policy using two tax principles, namely simplicity and certainty. This research was conducted with a qualitative approach and qualitative data collection techniques through literature and field study. The results showed that although the tax allowance facility procedure has met the principle of neutrality, the facility had not effectively attracted investments because there is no shipyard industry using the facility. Perceived time cost and psychological burden still incurred by the taxpayers that made this policy inefficient. In addition, this facility did not meet adequacy, responsiveness, simplicity, and certainty criteria. This facility was also not appropriate for the shipyard industry because the tax allowance could only be utilized by large-scale industries, while small and medium-scale industries could not utilized the tax allowance facility.